If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(8x + 4) = 4x + -2(6x + 2) Reorder the terms: -1(4 + 8x) = 4x + -2(6x + 2) (4 * -1 + 8x * -1) = 4x + -2(6x + 2) (-4 + -8x) = 4x + -2(6x + 2) Reorder the terms: -4 + -8x = 4x + -2(2 + 6x) -4 + -8x = 4x + (2 * -2 + 6x * -2) -4 + -8x = 4x + (-4 + -12x) Reorder the terms: -4 + -8x = -4 + 4x + -12x Combine like terms: 4x + -12x = -8x -4 + -8x = -4 + -8x Add '4' to each side of the equation. -4 + 4 + -8x = -4 + 4 + -8x Combine like terms: -4 + 4 = 0 0 + -8x = -4 + 4 + -8x -8x = -4 + 4 + -8x Combine like terms: -4 + 4 = 0 -8x = 0 + -8x -8x = -8x Add '8x' to each side of the equation. -8x + 8x = -8x + 8x Combine like terms: -8x + 8x = 0 0 = -8x + 8x Combine like terms: -8x + 8x = 0 0 = 0 Solving 0 = 0 Couldn't find a variable to solve for. This equation is an identity, all real numbers are solutions.
| 2-x+3=-(x-1) | | 0.15x=4.5 | | 0.15x=7.2 | | 4(4-3x)=4x+6 | | .10-15=21 | | -4x+6=-2(-3x+9) | | 3x+6-2=x+14 | | 3(x-5)+5+2=4(x+4)+5 | | 3r^2-26r+48=0 | | 3x-36=5x-145 | | 19=3a | | 3x+7=14+4x | | -4(2x-6)=16 | | x/6=6 | | 7(x+3)=7(x-4) | | 8a=300 | | 15+b= | | a(49-14h+h^2)+k=2700 | | 12(x-3)=-3(12-4x) | | 0.68x=1513 | | 12x-1=29x-1 | | 6x+2=2(x+9) | | -4=x-7 | | 3X(4+2X)=43 | | 2(x-2)-3(4x+3)=-13 | | 30n^2*b-87nb+30b= | | 7+x=-1 | | -3=x-7 | | 0.68x=3468 | | 0.2(x+0.4)=0.4(x-4.8) | | x-2=1246 | | -1.5x+7.1=2.6 |